NDASMU IN PRABOWO SUBIANTO’S POLITICAL SPEECH: AN ANALYSIS OF EXPRESSIVE SPEECH ACT AND NETIZENS’ RESPONSES - Putri, Desti Eni Ananda; Rahmawati, Sophia (IdeBahasa, 2025)
This study aims to analyze the expressive speech acts contained in the utterance “ndasmu” delivered by Indonesia’s 8th President, Prabowo Subianto, during a political speech at the 17th anniversary of the Gerindra Party. The data were obtained from the video of the speech and comments from netizens on social media platforms. The theoretical framework is based on Searle’s (1979) theory of expressive speech acts, which views such utterances as reflections of the speaker’s psychological state toward a specific situation. This research employed a descriptive qualitative method. Data were collected through documentation and observation, while the analysis involved categorizing netizen responses into positive, negative, and humorous reactions. The findings reveal that the utterance “ndasmu” is a spontaneous emotional expression representing displeasure, which received a variety of responses from the public. These responses demonstrate how expressive speech acts in political communication can trigger broad social reactions and contribute to digital political discourse.